PROBLEMATIKA PEMBATALAN PENGUCAPAN IKRAR TALAK DI PENGADILAN AGAMA - Ahmad Jamaludin (Media Nusantara, 2018)
Pronounce the pledge of talak has a very important position in the divorcepetition filed by a husband against his wife in the Religious Court. When ahusband does not make a pledge of divorce for reasons of reconciliation with hiswife then it is very good for their marital relationship. But when a husband doesnot pronounce the pledge of talak for reasons of slowing down and stalling thetime for divorce does not occur so the pledge of divorce slips and his marital bond remains intact. This phenomenon is the cause of legal uncertainty and there is no sense of justice for the wife. The purpose of this research is to (1) know and analyze the arrangement of the cancellation of pronunciation of ikrar talak in the religious court (2) to know and analyze how the legal effect on the cancellation of pledge of pledge of talak in religious court with normative juridical method. The results of this study indicate that (1) the arrangement of cancellation of pronouncement of pledge of talak in religious court has been regulated in Article 131 Compilation of Islamic Law but not set in detail administrative sanction given to husband when husband did not pledge for reasons of stalling the time of divorce and (2) the legal consequences of the cancellation of the pledge of the vow of talak in religious court may result in legal uncertainty and injustice for the wife due to the absence of a divorce so that the household ties remain intact and there is no sanction for the husband. The benefits of this research are to contribute in the form of empirical thoughts and findings, especially regarding the practice of pledge of talak in religious courts.